Evaluation of spectral photon counting computed tomography K-edge imaging for determination of gold nanoparticle biodistribution in vivo. Issue 46 (20th July 2017) - Si-Mohamed, Salim; Cormode, David P.; Bar-Ness, Daniel; Sigovan, Monica; Naha, Pratap C.; Langlois, Jean-Baptiste; Chalabreysse, Lara; Coulon, Philippe; Blevis, Ira; Roessl, Ewald; Erhard, Klaus; Boussel, Loic; et al.
Abstract : A new spectral photon-counting CT prototype has the potential for non-invasive quantitative determination of gold nanoparticle biodistribution in vivo over time. Abstract : Spectral photon counting computed tomography (SPCCT) is an emerging medical imaging technology. SPCCT scanners record the energy of incident photons, which allows specific detection of contrast agents due to measurement of their characteristic X-ray attenuation profiles. This approach is known as K-edge imaging. Nanoparticles formed from elements such as gold, bismuth or ytterbium have been reported as potential contrast agents for SPCCT imaging. Furthermore, gold nanoparticles have many applications in medicine, such as adjuvants for radiotherapy and photothermal ablation. In particular, longitudinal imaging of the biodistribution of nanoparticles would be highly attractive for their clinical translation. We therefore studied the capabilities of a novel SPCCT scanner to quantify the biodistribution of gold nanoparticles in vivo . PEGylated gold nanoparticles were used. Phantom imaging showed that concentrations measured on gold images correlated well with known concentrations (slope = 0.94, intercept = 0.18, RMSE = 0.18, R 2 = 0.99). The SPCCT system allowed repetitive and quick acquisitions in vivo, and follow-up of changes in the AuNP biodistribution over time. Measurements performed on gold images correlated with the inductively coupled plasma-optical emission spectrometry (ICP-OES) measurements in the organs of interest (slope = 0.77, intercept = 0.47, RMSE = 0.72, R 2 = 0.93). TEM results were in agreement with the imaging and ICP-OES in that much higher concentrations of AuNPs were observed in the liver, spleen, bone marrow and lymph nodes (mainly in macrophages). In conclusion, we found that SPCCT can be used for repetitive and non-invasive determination of the biodistribution of gold nanoparticles in vivo .